2017
DOI: 10.1007/s11368-017-1728-y
|View full text |Cite
|
Sign up to set email alerts
|

An overlooked nitrogen loss linked to anaerobic ammonium oxidation in estuarine sediments in China

Abstract: Purpose Despite its importance, anammox (anaerobic ammonium oxidation) in estuarine sediment systems remains poorly understood, particularly at the continental scale. This study aimed to understand the abundance, diversity, and activity of anammox bacteria and to determine the main factors influencing the anammox process in estuarine sediments in China. Materials and methods Estuarine sediments were collected from 18 estuaries spanning over 4000 km. Experiments using an 15 N-tracer, quantitative PCR, and clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…It can be speculated that higher TN concentration may provide an environment favorable for the distribution and growth of anammox bacteria ( Shen et al, 2016 ). In line with other studies ( Metz et al, 2003 ; Etchebehere and Tiedje, 2005 ; Yang et al, 2017 ), a positive correlation between anammox activity and abundance ( hzsB or 16S rRNA gene) was not observed. These results indicated that anammox rates are limited not by the presence of the population capable of anammox but by the availability of or as substrate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It can be speculated that higher TN concentration may provide an environment favorable for the distribution and growth of anammox bacteria ( Shen et al, 2016 ). In line with other studies ( Metz et al, 2003 ; Etchebehere and Tiedje, 2005 ; Yang et al, 2017 ), a positive correlation between anammox activity and abundance ( hzsB or 16S rRNA gene) was not observed. These results indicated that anammox rates are limited not by the presence of the population capable of anammox but by the availability of or as substrate.…”
Section: Discussionsupporting
confidence: 91%
“…Candidatus Scalindua was almost the only genus found in marine sediments, such as South China Sea ( Hong et al, 2011a ), Bohai Sea ( Dang et al, 2013 ), and Arabian Sea ( Woebken et al, 2008 ). In contrast to marine environments, all of these genera of anammox bacteria have been detected in soil ecosystems ( Wang et al, 2015 ; Yang et al, 2017 ). Zhu et al (2011) found that the 16S rRNA gene sequence of fertilized paddy soil were related to four different genera of anammox bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many different environmental factors can affect anammox bacterial diversity and distribution. For example, temperature was a key environmental factor shaping the distribution and diversity of anammox bacteria in the coastal estuaries of China ( Yang et al, 2017 ). Organic carbon influenced the distribution of anammox bacteria in Qiantang River sediments ( Hu et al, 2012 ) and Yangtze estuary marsh sediment ( Hou et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ca . Brocadia possesses metabolic diversity and could make better use of organic compounds for energy than most other anammox bacteria (Gori, Tringe, Kartal, Marchiori, & Jetten, 2011; Yang et al, 2017). This metabolic diversity may explain why Ca .…”
Section: Discussionmentioning
confidence: 99%